The effect of elevated temperatures on the mechanical properties of laminated bamboo. (30th November 2019) - Xu, Ming; Cui, Zhaoyan; Tu, Liuhui; Xia, Qiuling; Chen, Zhongfan
Highlights: The effect of temperature and grain direction on compressive and tensile properties of laminated bamboo was presented. Stress-strain relationship of laminated bamboo at elevated temperatures were reported. The equations with reduction factors for strength and modulus of elasticity were established. Abstract: The steady-state test method is employed to determine the stress-strain relationship and reduction factors for the strength and elastic modulus of laminated bamboo in different directions at temperatures from 20 °C to 280 °C. The experimental results indicate that the compressive stress-strain curves of the laminated bamboo have pronounced elastic deformation stage, plastic deformation stage and descending stage. The compressive strength and elastic modulus of the bamboo in both the flatwise and edgewise directions are similar, and the compressive strength and elastic modulus decrease with increasing temperature from 20 °C to 280 °C. The tensile stress-strain relationship of the bamboo is generally linear from loading to failure, and the failure is obviously brittle. The tensile strength and elastic modulus of the bamboo in both the flatwise and edgewise directions are similar, and the tensile strength and elastic modulus decrease with increasing temperature. A formula describing the stress-strain relationships of the bamboo is proposed. Compared with the bamboo scrimber and timber specifications in Eurocode 5 and the literature, the reduction factors of laminated bamboo have a similar change tendency with those of the timber addressed in Eurocode 5, but the rules are not fully applicable for laminated bamboo. The formulas for the tensile and compressive strength and elastic modulus reduction factors of the bamboo with temperature are statistically regressed and established. This work provides an important reference to understand and predict the performance of laminated bamboo members in fire conditions.